Religion in schools learning lessons from Wales. - SANDBERG, RUSSELL (Anthem studies in law reform, 2022)
To what extent should religion be taught in classrooms? Should lessons also cover non-religious beliefs? Should the teaching of religion be compulsory or should it be a matter of choice by the parents or the child? Should faith schools be allowed to teach their religious beliefs? Should religious worship be compulsory for all pupils? Questions of how religion operates within schools prove controversial and divisive. This book explores radical changes that are being made in Wales and the lessons that can be learnt. It examines the historical development of the law in this area, the new Welsh law, its potential shortcomings and areas that the new law leaves untouched, namely the rules on religious worship. The book is written by a leading authority on the interaction of law and religion whose work fed into Welsh parliament debates on the Curriculum and Assessment (Wales) Act 2021.